Exploiting subtractive genomics to identify novel drug targets and new immunogenic candidates against Bordetella pertussis: an in silico study - Khazani Asforooshani, Mahshid; Noori Goodarzi, Narjes; Shahbazi, Behzad; Rezaie Rahimi, Nayereh; Mahdavian, Kimia; Rohani, Mahdi; Badmasti, Farzad (Frontiers in Bioinformatics, 2025)
BackgroundBordetella pertussis, the causative agent of whooping cough, remains a significant global health concern despite the widespread availability of vaccines. The persistent reemergence of pertussis is driven by the bacterium’s ongoing genomic evolution, shifting epidemiological patterns, and limitations in current vaccine strategies. These challenges highlight the urgent need to identify novel drug targets and immunogenic candidates to enhance therapeutic and preventive measures against B. pertussis.MethodsIdentification of novel drug targets and the detection of immunogenic factors as potential vaccine candidates were performed. Cytoplasmic proteins were evaluated for their similarity to the human proteome, metabolic pathways, and gut microbiota. On the other hand, surface-exposed proteins were evaluated as immunogenic targets using a reverse vaccinology approach. A multi-epitope vaccine (MEV) was designed based on the immunogenic linear B-cell epitopes of three autotransporters and the beta domain of SphB2 as a scaffold for MEV. Molecular docking, immune simulation results, and molecular dynamics simulations were performed to evaluate the binding affinity and feasibility of interaction between chimeric MEVs and immune receptors.ResultsSix proteins were identified as excellent potential drug targets, including elongation factor P (WP_003810194.1), Aspartate kinase (WP_010930633.1), 50S ribosomal protein L21 (WP_003807462.1), Homoserine dehydrogenase (WP_003813074.1), Carboxynorspermidine decarboxylase (WP_003814461.1), and PTS sugar transporter subunit IIA (WP_010929966.1). On the other hand, reverse vaccinology identified nine immunogenic proteins, including BapA (WP_010930805.1), BrkA (WP_010931506.1), SphB2 (WP_041166323.1), TcfA (WP_010930243.1), FliK (WP_041166144.1), Fimbrial protein (WP_010930199.1), TolA (WP_010931418.1), DD-metalloendopeptidase (WP_003811022.1), and an I78 family peptidase inhibitor protein (WP_003812179.1). SphB2-based MEV was designed using six linear B-cell epitopes of the extracellular loops of the autotransporters. The binding affinity and feasibility of the interaction between MEV and TLR2, TLR4, and HLA-DR-B were computationally confirmed by molecular dynamics.ConclusionIt appears that proteins involved in translation and metabolism can be considered novel drug targets. Furthermore, this study highlights autotransporter proteins as promising immune targets. There is no doubt that experimental work should be conducted to confirm the results in the future.